Psychological profile of infertile couples eligible for in vitro fertilization - Diego Ramón Hernández Fernández; Yisel Alé Otero (Acta Médica del Centro)
Introduction: infertility is a health condition with an emotional impact on the couple accompanied by an increase in psychological distress. In vitro fertilization is the most advanced assisted reproduction alternative that an infertile couple can access in Cuba. Objective: to describe the psychological profile of infertile couples undergoing in vitro fertilization treatments. Methods: an investigation was carried out with a prospective longitudinal quantitative-qualitative approach in infertile couples treated at the Provincial Center for low-complexity assisted reproduction of the “Mariana Grajales” Gynecobstetric Teaching Hospital in the period from January 2022 to June 2023. The sample it was made up of 21 couples that were selected through non-probabilistic sampling. Results: the sample was characterized by ages between 20 and 47 years, with an average in the third decade of life in both sexes. The presence of emotional alterations was determined, with a predominance of anxiety as a state at low and medium levels, the female sex is the most affected, and in the male sex a predominance of uncertainty was determined as the predominant emotional state. Conclusions: the psychological profile of the couples in the study is determined by emotional alterations, with a predominance of anxiety as a state at low and medium levels, the female sex was the most affected and in the male sex a predominance of uncertainty as a state was determined predominant emotional.